Pelaksanaan Pelayanan Kesehatan Gigi Dan Mulut Warga Binaan Pemasyarakatan Dalam Mewujudkan Derajat Kesehatan Optimal(Studi Kasus di Rumah Tahanan Negara Klas I Surakarta) - Putri, Suryasti; , drg. Ana Riolina, MPH; , drg. Budi Dewantari (2016)
Health is one of the factors to have a strong future generation. Everyone has the same right to health, including prisoners who are serving a criminal act in the house of detention or prison. Along with the increasing occupant in the house of detention and prisons are the most important thing is the provision of health care. Oral health is an integral part of general health. The symptoms in the mouth can be affected by a number of systemic diseases. Additionally, oral diseases can cause infection, inflammation and serious impact on general health. In order to achieve the highest health standard, it is necessary to mobilize the highest health care including oral health care. This study was conducted using descriptive method with quantitative approach through questionnaires and qualitative approach through documentation study. The aim of this study was to investigate the implementation of oral health care among the prisoners in the class I house of detention Surakarta in achieving the highest health standard. The number of respondents in this study were 28 respondents who had oral health care in January to December 2015 at class I house of detention polyclinic Surakarta and still past their detention at the time of the study. The results of this study described that oral health care of prisoners in the class I house of detention Surakarta has not been optimal. Majority of respondents were satisfied with the oral health care which the highest satisfaction lies in the assurance dimension but respondents were unsatisfied with the reliability dimension. Documentation study of oral health care prisoners standard based on the Minister of Justice and Human Rights of the Republic of Indonesia Number M.HH.02.UM.06.04 in 2011 could not be implemented fully by the class I house of detention Surakarta primarily on preventive and curative cares.